2021
DOI: 10.1093/ecco-jcc/jjab099
|View full text |Cite
|
Sign up to set email alerts
|

Upadacitinib Treatment Improves Symptoms of Bowel Urgency and Abdominal Pain, and Correlates With Quality of Life Improvements in Patients With Moderate to Severe Ulcerative Colitis

Abstract: Background and Aims Bowel urgency and abdominal pain are impactful, yet underappreciated ulcerative colitis symptoms and not commonly assessed in clinical trials. We evaluated how these symptoms may improve with upadacitinib treatment and correlate with clinical and health-related quality of life (HRQOL) outcomes in the phase 2b U-ACHIEVE study. Methods Patients aged 18–75 years with moderately to severely active ulcerative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…In the phase II upadacitinib trial, bowel urgency and QoL, measured by IBD questionnaire and Short Form-36, were assessed. Urgency correlated with disease activity, biomarkers, and QoL with improvements in urgency paralleling clinical response and remission (17,18). Specifically, an absence of urgency was associated with Mayo endoscopic remission, histologic remission, and mucosal healing with an OR of 3.6 (95% CI 1.8–7.2), 4.6 (95% CI 2.4–8), and 4.9 (95% CI 2.1–11.6), respectively, at week 12 (19).…”
Section: Discussionmentioning
confidence: 99%
“…In the phase II upadacitinib trial, bowel urgency and QoL, measured by IBD questionnaire and Short Form-36, were assessed. Urgency correlated with disease activity, biomarkers, and QoL with improvements in urgency paralleling clinical response and remission (17,18). Specifically, an absence of urgency was associated with Mayo endoscopic remission, histologic remission, and mucosal healing with an OR of 3.6 (95% CI 1.8–7.2), 4.6 (95% CI 2.4–8), and 4.9 (95% CI 2.1–11.6), respectively, at week 12 (19).…”
Section: Discussionmentioning
confidence: 99%
“… 53 Moreover, the oral administration route can improve patients’ quality of life, reducing the number of accesses to the hospital and lost workdays. 54 , 55 In fact, a significantly greater proportion of patients who responded to UPA induction phase maintained improvements in health-related quality of life (HRQOL) compared to placebo after 52 weeks of maintenance treatment.
Figure 1 Pros and cons of upadacitinib in patients with moderate-to-severe ulcerative colitis.
…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Several randomized, doubleblind, placebo-controlled trials have attempted to evaluate the efficacy and safety of tofacitinib, TD-1473, upadacitinib, filgotinib and peficitinib in patients with active UC. [16][17][18]20,21,24 All of these drugs have shown considerable efficacy in placebo-controlled trials, but the relative efficacy and safety of JAK inhibitors remain unclear due to a lack of head-to-head comparisons. When direct comparisons are not available, indirect comparisons through a network meta-analysis (NMA) can assist in generating evidence for decision-making.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Two previous network meta‐analyses have demonstrated that tofacitinib is effective for achieving clinical, endoscopic and quality of life outcomes compared to placebo in patients with UC 22,23 . Several randomized, double‐blind, placebo‐controlled trials have attempted to evaluate the efficacy and safety of tofacitinib, TD‐1473, upadacitinib, filgotinib and peficitinib in patients with active UC 16–18,20,21,24 . All of these drugs have shown considerable efficacy in placebo‐controlled trials, but the relative efficacy and safety of JAK inhibitors remain unclear due to a lack of head‐to‐head comparisons.…”
Section: What Is Known and Objectivementioning
confidence: 99%